Obstetrics outcome in pregnant women with cardiac disease in tertiary care center, Dehradun, India - Singh, Prachi; Saxena, Namrata; Gupta, Vineeta; Bansal, Neeta; Pehal, Yashika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Incidence of heart disease in pregnancy is about 1%. Pregnant patient with cardiac disease can present with lot of challenges for the obstetrician, paediatrician and the cardiologist. With improvement in diagnostic, medical, surgical management, more patient with cardiac diseases especially congenital are able to reach reproductive age. Therefore, still a cardiac disease remains a significant cause of maternal death. Maternal and fetal prognosis both is affected by the care given and the skills used in the treatment of the individual patient. Hospital has resulted in majority of cardiac disease patient being managed in a tertiary care center and this provide an opportunity to report on clinical experiences of pregnancy with cardiac disease, their management and obstetrical outcomes. Methods: This was a retrospective study, with all the patients detailed demographic information, diagnosis, course in the hospital, management, maternal and fetal outcome was obtained from the medical records and files. Results: Incidence of cardiac disease was found to be 0.7%, 47% of pregnant women fell in age group of 26-30 years, 38.2% were primigravida, only 23.53% were booked, and half of them belonged to NYHA II class. 73.5% had Rheumatic heart disease and the most common obstetrics complications were preterm labor and anemia. LSCS was done in 29.4% cases and 38.2% of the newborns were premature. Conclusions: Prematurity anaemia, IUGR, are the common obstetrical complication in pregnant patient with cardiac disease which can be taken care with increased awareness and pre-conceptional counselling especially in patient with congenital heart disease. For optimization of maternal and neonatal outcomes in these patients, dedicated team of obstetrician, fetal medicine specialist, pediatricians, cardiologist and anesthesiologist is the prime requirement.